IDENTIFIKASI RUANG PUBLIK DI LINGKUNGAN BANDARA ADI SUMARMO SEBAGAI ART SPACE - Sulistyani, Harmilyanti (Acintya, 2014)
The mobility of human being needs a transit space. Airport as a transit space or terminal has a facilityto support the activity of the air traffic. Based on the activity, space on the airport is divided intoseveral criteria. There are public area, private area and service area.Public area is a space that canbe acces by visitor with or without requirement. Airport public space is different from another terminalpublic space. This research uses graphic analysis with interpretation discription. Graphic analysis isused to identify the room visual structure. Interpretative analysis is used to explore the connection ofform and room function. Public space on Adi Sumarmo Airport can be used as an art space due to thestatus as International airport and commercial airport.Keywords: Adi Sumarmo Airport, public space, art space, commercial airport, transit space